2012
DOI: 10.1007/s00432-011-1137-3
|View full text |Cite
|
Sign up to set email alerts
|

miR-181a sensitizes resistant leukaemia HL-60/Ara-C cells to Ara-C by inducing apoptosis

Abstract: This study for the first time demonstrated that downregulation of miR-181a and upregulation of Bcl-2 in leukaemia cells confer resistance to Ara-C-based therapy. These results suggest that restoration of miR-181a expression might provide a promising therapeutic in drug resistance of leukaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 26 publications
5
38
0
Order By: Relevance
“…Likewise, MIR181A was able to affect ATG5 levels and autophagy in K562 agents Ara-C, vincristine and cisplatin in glioma, leukemia, gastric cancer or lung cancer cell lines. 33,34,58,59 Similarly, we could observe that MIR181A overexpression potentiated the toxicity of the cancer therapy agent cisplatin in MCF-7 breast cancer cells (Fig. S10).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Likewise, MIR181A was able to affect ATG5 levels and autophagy in K562 agents Ara-C, vincristine and cisplatin in glioma, leukemia, gastric cancer or lung cancer cell lines. 33,34,58,59 Similarly, we could observe that MIR181A overexpression potentiated the toxicity of the cancer therapy agent cisplatin in MCF-7 breast cancer cells (Fig. S10).…”
Section: Discussionmentioning
confidence: 69%
“…BCL2, an antiapoptotic member of the BCL2 family that was involved in autophagy regulation through sequestration of the autophagy protein BECN1, is among the known targets of MIR181A. [31][32][33][34] In our system, overexpression of the miRNA did not significantly affect the levels of BCL2 protein under nonstarved or starved conditions in MCF-7 cells (Fig. S6A), whereas, in line with other starvation was more prominent after Ant-181a transfection compared with controls (Fig.…”
Section: Mir181a Blocked Starvation-induced Autophagy In Mcf-7mentioning
confidence: 84%
“…28 Recently, it was shown that ectopic expression of miR-181a sensitizes AML cell lines to chemotherapy. 29 In addition, we reported that higher miR-181a expression was associated with the presence of CEBPA mutations in CN-AML patients. 5 In this study, we show that higher miR-181a expression in CN-AML patients is predominantly present in the patients harboring CEBPA N-terminal mutations, as opposed to those having single C-terminal mutations or wild-type CEBPA.…”
mentioning
confidence: 96%
“…43,44 Recently, it was demonstrated that miR-181a can sensitize a chemotherapyresistant HL60 cell line to Ara-C treatment. 29 Having found that miR-181a is up-regulated in response to lenalidomide, we asked whether pretreatment of AML cells with this compound can similarly sensitize the cells to Ara-C.When THP-1 cells were treated with either 3M lenalidomide, 1M Ara-C, or both compounds simultaneously, an additive cytotoxic effect was observed ( Figure 6A). Using THP-1 cells transiently transfected with antagomiR-181a, or a nonsilencing control oligoribonucleotide, we asked whether the lenalidomide effect was mediated by miR-181a expression.…”
mentioning
confidence: 99%
“…One group showed that downregulation of miR-181a and subsequent upregulation of Bcl-2 in leukemia cells drove chemoresistance to Ara-C, 63 one of the most common drugs used in AML. The introduction of this miRNA into the cells increased chemosensitivity via apoptosis.…”
Section: The Future Of Therapy Related To Mirnamentioning
confidence: 99%